On Picture Fuzzy Sets - ARAB, cheyma; Supervisor: Amroune, Abdelaziz (UNIVERSITY of M'SILA, 2022)
The objective of this memory is to assimilate the notion of picture fuzzy sets (PFS) as well as some properties and operations related to this notion.
Keywords: picture fuzzy sets: operations related